Occurrence and diversity of Campylobacter species in diarrheic children and their exposure environments in Ethiopia. - Dinaol Belina; Tesfaye Gobena; Ameha Kebede; Meseret Chimdessa; Bahar Mummed; Cecilie Amalie Neijendam Thystrup; Tine Hald (PLOS Global Public Health)
Campylobacter is a major zoonotic foodborne pathogen that poses a significant public health threat, particularly among children and immunocompromised individuals. However, data on the occurrence and sources of Campylobacter infection remain scarce in Ethiopia. This study assessed the occurrence, diversity, and relationships between Campylobacter from diarrheic children and potential exposure sources using whole-genome sequencing. Through case-based tracing, animal, food, and environmental samples were collected from Harar town and Kersa district between November 2021 and January 2023. Campylobacter was identified using selective media, and DNA was extracted and sequenced with the Illumina NextSeq 550 instrument. Sequence reads were analysed using bioinformatics tools. The overall Campylobacter prevalence in the exposure sources was 5.5%, with 6.0% in urban and 5.0% in rural settings. Campylobacter detection was 1.8 times more likely in household samples (8.7%; OR = 1.8; 95% CI: 0.7-4.5) than in samples from marketplaces. The occurrence of Campylobacter in food was 4.2%, with no significant differences across the meat, milk, and other food categories. The likelihood of Campylobacter contamination in the environment was 5.8 times higher in the presence of poultry (17.7%; OR = 5.8; CI: 1.1-30.6) compared to shoats. Sequence analysis identified a low Campylobacter spp. diversity comprising only C. jejuni and C. coli, which were characterized by 8 distinct sequence types (STs). Phylogenetically, the majority of the sequenced case isolates were clustered with isolates from either caretakers, environmental exposures, or both. In conclusion, Campylobacter was detected in various exposure sources of diarrheic children, and its occurrence did not differ significantly between Kersa and Harar or among food items. The majority of isolates shared MLST profiles and clustered together, demonstrating the involvement of multiple vectors in the transmission of the pathogen. Genome-based integrated studies supported by an attribution model are recommended to determine the relative contribution of each source.